2018
DOI: 10.1007/s10143-018-0999-0
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculostomy-related hemorrhage in patients on antiplatelet therapy for endovascular treatment of acutely ruptured intracranial aneurysms. A meta-analysis

Abstract: The risk of ventriculostomy-related hemorrhage among patients requiring antiplatelet therapy (AT) for the endovascular treatment of acutely ruptured intracranial aneurysms needed further investigation. The authors performed a systematic review and meta-analysis of the literature examining the EVD-related hemorrhage rate among patients with and without AT (controls). According to PRISMA guidelines, a comprehensive review of studies published between January 1990 and April 2018 was carried out. The authors ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Periprocedural thrombosis, and subsequent antiGP2b3a administration remains a risk factor for ischemic complications. Regarding maintenance therapy, although DAPT is more protective against ischemic events after SAC [29,30], it is probably more dangerous, in particular with loading doses [31,32]. The optimal balance between thrombosis and hemorrhage remains unknown; this study states the low risk of ischemic complications in both SAPT and DAPT regimens and may be useful to tailor the treatment on a singlepatient basis.…”
Section: Post-operative Ischemic Complicationsmentioning
confidence: 86%
“…Periprocedural thrombosis, and subsequent antiGP2b3a administration remains a risk factor for ischemic complications. Regarding maintenance therapy, although DAPT is more protective against ischemic events after SAC [29,30], it is probably more dangerous, in particular with loading doses [31,32]. The optimal balance between thrombosis and hemorrhage remains unknown; this study states the low risk of ischemic complications in both SAPT and DAPT regimens and may be useful to tailor the treatment on a singlepatient basis.…”
Section: Post-operative Ischemic Complicationsmentioning
confidence: 86%
“…Another finding by Cagnazzo et al, later confirmed by Lim et al, was that performing EVD before endovascular coiling was effective at minimizing the risk of ventriculostomy-related hemorrhagic complications and was not associated with a higher risk of rebleeding or other EVD-related complications, but anti-platelet therapy and stent placement are still independent risk factors for hemorrhagic complications. 51,52 Nonetheless, Roh et al discovered that SAC patients only have a slightly higher, but clinically insignificant, rate of EVD-related hemorrhagic complications compared to endovascular coiling alone and that stent use is not an independent risk factor for EVD-related hemorrhage. 33 In our systematic review, 245 EVDs were inserted and resulted in 33 (13.5%) EVD-related hemorrhages compared to the 10% EVD-related hemorrhage reported by Bodily et al 41 Most articles did not specify if the EVDrelated hemorrhages occurred in those who received EVD before stenting or after stenting, thus we could not determine if there was a temporal relationship between EVD-related hemorrhage and stenting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of intravascular stents, and, in particular, the high metal-density flow diverters, requires the use of DAPT to prevent stent thrombosis and ischaemic complications. This, in turn, increases the risk and severity of haemorrhagic complications in patients with acutely ruptured aneurysms 8. The phosphorylcholine coating of the PED-Shield device has been shown to reduce platelet adhesion and activation 9.…”
Section: Discussionmentioning
confidence: 99%